Strengthening transparency of political party financial reports to prevent illegal fundraising - Rino Irlandi (Integritas: Jurnal Antikorupsi, 2024)
Political parties get their financial resources from membership fees, legitimate donations, and APBN/APBD. However, in the corruption case that implicate Abdul Gafur Mas'ud and Rahmat Effendi, political parties allegedly used the proceeds from corruption as one of their financial sources. Through the doctrinal legal research method, this research traces the financial sources of political parties to investigate these allegations. The results show that the financial sources of political parties are difficult to access. This shows that political parties are not transparent in reporting their finances. This is due to the lack of regulations regarding the financial transparency of political parties. As a result, corruption funds become one of their financial sources. Therefore, it is necessary to improve the transparency rules of political party financial reports by: (1) requiring political party financial reports to be audited and reported to BPK annually and announced to the public; and (2) tightening sanctions for political parties that do not report overall finances. The sanctions can be in the form of a ban on participating in the next general election period.